O estágio supervisionado do curso de Pedagogia na formação de professora e professor - OLIVEIRA, Lorena Araújo (2022)
The research of the Course Completion Work is the result of the Supervised Internship in Elementary School Initial Years of the Pedagogy Course regarding teacher and teacher training as a theoretical-practical process. In the Pedagogy course of the Faculty of Education, University Campus of Bragança of the Federal University of Pará, the internship is a curricular activity, organized in the nucleus of deepening and diversification of studies in the axis of teacher training and organization of pedagogical practice. It is an initial training of professionals to work in the teaching of Early Childhood Education, Elementary School Early Years, Youth and Adult Education, educational management, pedagogical coordination, in a non-school environment. The guiding problem of the study is to know how the didactic-pedagogical activities of the Supervised Internship articulate academic training with professional practice in the initial training of teacher and professor of the Pedagogy Course of the Faculty of Education? The main objective is to analyze the didactic-pedagogical activities of the Supervised Internship, linking academic training with professional practice in the initial training of teacher and professor of the Pedagogy Course of the Faculty of Education. The curricular activity was developed at Escola Antônia Cunha Vila Jaburu-Primavera-PA, Municipality of Capanema, in a class of the 5th year/9. The research has a qualitative approach of the interactional type, carried out in stages, as provided for in the Supervised Internship Teaching Plan, using the technique of participant observation, interview, elaboration and execution of pedagogical practices in the regency of the classroom. The pedagogical technician and supervisor of the granting school participated. The results indicate that the Supervised Internship is a research activity, a moment of collaborative activities, time for professional training of the pedagogue and pedagogue. Moment of learning and exchange of experiences and educational practice in the school context. I conclude that it is necessary for the Municipal Education Department of Capanema and the School to consider reviewing the choice of publisher and the use of the Textbook in the teaching and learning process in the school context. In the same way that in the initial training of teachers and professors, there is a dialogue about the contents indicated in the southern view of publishers used in the Educational Departments of the Amazon Region. The Didactic Books of the researched School do not contemplate Law 10.639/2003 3 to 11.645/2008, which deals with Afro-Brazilian and indigenous culture. In summary, the context of the COVID-19 pandemic shows the limitations of the pedagogical work and the absence of planning for the resumption of face-to-face classes.